Affective Assessment Tools Development in Biology Subjects for X Grade in State High School. Issue 1 (March 2021) - Pratama, D J; Edi, S; Syarifuddin,
Abstract: This study aims to develop affective assessment tools in high school grade X Biology subject. The instrument developed will be tested for validity, reliability and practicality. The research was conducted at SMAN 1 and SMAN 2 Tanjungbalai. The development of affective domain assessment instruments is carried out using the 4-D model which is carried out in stages. The stage consists of Define, Design, Development and Dissemination. The result of research consisted of valid, practical and reliable affective assessment instruments that can be used to conduct affective assessments in schools. Validation value of the affective domain assessment instrument is 90.5%, categorized as good and worthy of use.